Training and visit extension in practice - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
Training and Visit Extension in Practice, edited by John Howell 1988, 107pp price UKL 4.95. ISBN 085003106 0.